PENGALAMAN GURU MERANCANG ASESMEN DIAGNOSTIK UNTUK MENDUKUNG PEMBELAJARAN BERDIFERENSIASI PADA PAI SEKOLAH DASAR - Okta Rosfiani; Batara Giflan Khairan; Gina Azizah; Khayla Adhani; Cecep Maman Hermawan (STAI Nusantara Kota Banda Aceh, 2026)
The Merdeka Curriculum positions diagnostic assessment as the starting point for designing differentiated instruction, yet how teachers actually build this practice from field experience—particularly in Islamic Religious Education (PAI) at the elementary level—remains underexplored. This study aims to describe and interpret teachers' experiences in designing cognitive and non-cognitive diagnostic assessments to support differentiated learning at SD Rawa Buntu 03. A qualitative approach with an instrumental case study design was employed. Data were collected through semi-structured interviews with three teachers whose teaching experience ranged from eight to more than fifteen years, complemented by field notes and observation results. Data were analyzed using the reduction, display, and conclusion-drawing model of Miles, Huberman, and Saldaña. The findings show that teachers developed informal non-cognitive assessments based on spontaneous behavioral observation to map student character, alongside cognitive assessments using rotating oral tests to map students' Qur'anic reading and writing abilities. These mapping results were followed up through learning grouping, peer tutoring, intensive out-of-class guidance, and flexible task deadlines. A notable anomaly emerged: the most effective non-cognitive assessment arose from the teacher's spontaneous improvisation rather than from a pre-designed formal instrument. This study contributes to strengthening the concept of contextual non-cognitive diagnostic assessment within PAI instruction and recommends developing a systematic, replicable informal observation guideline.